P-120 POLYMORPHISMS OF HLA (LOCI DR 4*) IN HISPANICS AS RISK FACTOR FOR DE-NOVO AUTOIMMUNE HEPATITIS AFTER LIVER TRANSPLANTATION - Adriana Varon Puerta; Luisa Fernanda Santos Cuervo; Oscar Alfredo Beltran Galvis; Martin Alonso Garzon Olarte; Cristina Torres; Jairo Rivera; Gilberto Andres Mejia (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: De-novo Autoimmune Hepatitis (De-novo AIH) after Liver Transplantation (LT) is considered rare. Its importance relies in a severe clinical course, with graft loss, non-response to immunosuppressants and need for retransplantation. The HLA (loci DR 3 and DR 4) has been associated with De-novo AIH especially in children in India.The objective was to determine the allelic frequencies of HLA (loci DR 3 * and DR 4 *) in donor livers of an adult population of patients with LT and its association with De-novo AIH. Patients / Materials and Methods: Retrospective observational study of cases and controls. 260 adult LT recipients were included. Cases were defined as histological confirmation of AIH De-novo after LT, controls were LT recipients free of the disease.The proportion of exposed cases was compared with the corresponding proportion in the control group. Results and Discussion: It is found that the frequency expressed as a percentage of individuals with the characteristic (HLA DR4 and De-novo AIH) is higher in the group of cases than in the control group, so it can be assumed a statistically significant association between the presence of HLA DR 4 in the donor and development of AIH De-novo after LT.8 cases were confirmed. All presented alterations of liver function tests with necroinflammatory pattern during the first 3 months after transplantation despite levels of immunosuppression within therapeutic ranges and all possible causes of alteration of the hepatic profile were ruled out. Despite appropriate management all of them developed cirrhosis and indication of retransplantation. Conclusions: AIH De-novo after LT is a real challenge for LT programs. Recent evidence demonstrating this type of genomic association with post-transplant diseases arouses the need for new management in line with Future, Precision or Personalized Medicine, where molecular biology and genetics play a crucial role in individualized therapies reducing costs avoiding unnecessary expenses to the health system.